2021
DOI: 10.1002/cjoc.202000515
|View full text |Cite
|
Sign up to set email alerts
|

Discover the Post‐Translational Modification Proteome Using Mass Spectrometry

Abstract: Protein post‐translational modifications (PTMs) are chemical modifications on proteins. PTMs play a key role in many cellular processes by influencing the structure of proteins and dynamically regulating their functions. Therefore, characterizing PTMs at proteome level is critical to provide invaluable insight into the functions of proteins underlying different biological processes. Advances in modern proteomics technologies including sample preparation, chromatography separation as well as mass spectrometry h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…2,127 genes were annotated in the GO database, mainly in metabolic function, cellular process, cell membrane, cell membrane components, catalytic activity, gene, and binding. Protease genes do not have biological functions after transcription and translation to form proteins, rather only after modification by a series of chemical reactions, such as ubiquitination, phosphorylation, acetylation, glycosylation, methylation, or lipidylation, can there be more protein types with complex structures, precise regulation, specific action, and perfect function [ 44 ]. In this study, COG function prediction, KEGG metabolic pathway annotation, and GO annotation of the genes encoded by this strain showed normal gene transcription and translation and a relatively high number of annotated genes, which indicated that the enzyme metabolism of this bacterium is active.…”
Section: Discussionmentioning
confidence: 99%
“…2,127 genes were annotated in the GO database, mainly in metabolic function, cellular process, cell membrane, cell membrane components, catalytic activity, gene, and binding. Protease genes do not have biological functions after transcription and translation to form proteins, rather only after modification by a series of chemical reactions, such as ubiquitination, phosphorylation, acetylation, glycosylation, methylation, or lipidylation, can there be more protein types with complex structures, precise regulation, specific action, and perfect function [ 44 ]. In this study, COG function prediction, KEGG metabolic pathway annotation, and GO annotation of the genes encoded by this strain showed normal gene transcription and translation and a relatively high number of annotated genes, which indicated that the enzyme metabolism of this bacterium is active.…”
Section: Discussionmentioning
confidence: 99%
“…The principle and representative examples are displayed in Figure 3 . As summarized in a recent review article, a variety of functional materials have been investigated, including magnetic and mesoporous materials, metal frame compounds, graphene, and dendrimers 38 .…”
Section: Nanotechnology-enabled Targeted and Non-targeted Proteome An...mentioning
confidence: 99%
“…[ 16‐19 ] Although mass spectrometry‐based detection methods improve the sensitivity of the assay, they require expensive and complex instrumentation as well as complicated sample pretreatment, which greatly increases the workload of researchers. [ 20‐24 ]…”
Section: Background and Originality Contentmentioning
confidence: 99%